A Novel Broad-Spectrum Elastase-Like Serine Protease From the Predatory Bacterium Bdellovibrio bacteriovorus Facilitates Elucidation of Site-Specific IgA Glycosylation Pattern - Bratanis, Eleni; Lood, Rolf (Frontiers in Microbiology, 2019)
The increased interest in predatory bacteria due to their ability to kill antibiotic resistant bacteria has also highlighted their inherent plethora of hydrolytic enzymes, and their potential as natural sources of novel therapeutic agents and biotechnological tools. Here we have identified and characterized a novel protease from the predatory bacterium B. bacteriovorus: BspE (Bdellovibrio elastase-like serine protease). Mapping preferential sites of proteolytic activity showed a single proteolytic cleavage site of native plasma IgA (pIgA) in the Fc-tail; as well as in the secretory component (SC) of secretory IgA (SIgA). Proteolysis of other native immunoglobulins and plasma proteins was either absent (IgG1 and 2, IgM, albumin and orosomucoid) or unspecific with multiple cleavage sites (IgG3 and 4, IgE, IgD). BspE displayed a broad activity against most amino acid bonds in shorter peptides and denatured proteins, with a slight preference for hydrolysis C-terminal of Y, V, F, S, L, R, P, E, and K. BspE autoproteolysis results in numerous cleavage products sustaining activity for up to 24h. The enzymatic activity remained stable at pH 5.0-9.0 but was drastically reduced in the presence of MnCl2 and completely inhibited by ZnCl2. The hydrolysis of pIgA was subsequently utilized for the specific glycan characterization of the released pIgA Fc-tail (Asn459). Besides contributing to the basic knowledge of Bdellovibrio biology and proteases, we propose that BspE could be used as a potential tool to investigate the importance, and biological function of the pIgA Fc-tail.